Entrevista com John Vogler - Vogler, Jonh; Silveira, José Renato Ferraz da; Zepeda, Claudio Andrés Téllez (InterAção, 2023)
The study of IR as a discipline tends to follow trends in actual international politics, so there was always some interest in environmental problems when they crossed national boundaries and caused disputes. Another concern was with natural resources as constituents of national power – this was arch Realist Hans Morgenthau’s concern. However, environment stayed at the periphery of IR for a very long time. What changed things was a rise in ‘green’ environmental politics within Western polities during the 1960s and an awareness that as well as transboundary problems, such as acid rain, there was a clear link to economic development. Such issues were at the heart of the first great UN environment conference held at Stockholm in 1972.